THE EFFECT OF MARKETING MIX ON PURCHASE DECISIONS FOR KUB CHICKEN DOC - Arif Cahyono; Dewi Masyithoh; Inggit Kentjowaty (Universitas Galuh, 2026)
The increasing national demand for animal protein encourages the development of superior local chickens as a sustainable food source. The Balitbangtan Superior Native Chicken, known as KUB chicken, has strong potential for development in smallholder poultry farming. Day Old Chick (DOC) of KUB chicken is a crucial production input because chick quality determines growth performance, health, and productivity in the next rearing phase. The biological nature of DOC makes purchasing decisions influenced not only by chick quality, but also by availability, distribution, service process, and consumer trust in the provider institution. This study aimed to identify consumer profiles and analyze the effect of the 7P marketing mix on purchasing decisions for KUB chicken DOC at the East Java Agricultural Implementation and Modernization Center (BRMP). This research used a quantitative descriptive method involving 100 respondents who purchased KUB chicken DOC during 2023–2025. Data were collected through an online Likert-scale questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics 26. The results showed that consumers were dominated by males (82%), aged 30–39 years (42%), senior high school/vocational school graduates (48%), and farmers (58%). A total of 79% of respondents had made repeat purchases. The average purchasing decision score was 13.90 ± 2.89, indicating a high category. The 7P marketing mix had a significant simultaneous effect on purchasing decisions (F = 3.558; Sig. = 0.002). Partially, only place (t = 2.971; Sig. = 0.004) and process (t = 2.313; Sig. = 0.023) had positive and significant effects. Marketing strategies should prioritize distribution strengthening, DOC availability assurance, clear ordering procedures, and service efficiency.